Synonymization of Calathea subg. Pseudophrynium ser. Polystachyae with a new combination in the genus Maranta (Marantaceae) - Braga, Joao Marcelo Alvarenga (Phytotaxa, 2014)
Calathea subgenus Pseudophrynium series Polystachyae was proposed to accommodate a single species, Calathea polystachya. This species is herein transferred to Maranta, recognizing the wide morphological re-delimitation of this genus.